Food quantity–quality co‐limitation: Interactive effects of dietary carbon and essential lipid supply on population growth of a freshwater rotifer. (15th March 2019) - Schälicke, Svenja; Sobisch, Lydia‐Yasmin; Martin‐Creuzburg, Dominik; Wacker, Alexander
Abstract: Food quantity and quality are highly variable in natural systems. Therefore, their interplay and the associated effects on consumer population growth are important for predator–prey interactions and community dynamics. Experiments in which consumers were exposed to elemental nutrient limitations along food quantity gradients suggest that food quality effects on consumer performance are relevant only at high food quantities. However, elemental nutrients act differently on physiological processes than biochemical nutrients. So far, the interactive effects of food quantity and biochemical compounds on consumer performance have been insufficiently studied. We studied interactive effects of food quantity and biochemical food quality on population growth, including fecundity and survival, of the freshwater rotifer Brachionus calyciflorus . We hypothesised that these life history traits are differently affected by the availability of biochemical nutrients and that food quality effects gain importance with increasing food quantity. In a first experiment, we established food quantity and quality gradients by providing rotifers with different concentrations of a low‐quality food, the sterol‐free cyanobacterium Synechococcus elongatus, supplemented with increasing amounts of cholesterol. In a second experiment, food quantity and quality gradients were established by providing different proportions of two prey species differing in biochemical food quality, i.e. S. elongatus and the lipid‐rich alga Nannochloropsis limnetica, at different total food concentrations. We found that the effects of cholesterol supplementation on population growth increased with increasing food quantity. This interactive effect on population growth was mainly due to food quality effects on fecundity, as effects on survival remained constant along the food quantity gradient. In contrast, when feeding on the mixed algal diet, the food quality effect associated with increasing the proportion of the high‐quality alga did not change along the food quantity gradient. The data on survival and fecundity demonstrate the missing interactive effect of food quantity and quality on population growth, as both traits were oppositely affected. Survival was affected by food quality primarily at low food quantity, whereas food quality effects on fecundity were stronger at high food quantity. Our results highlight the significance of essential biochemicals in mediating the interactive effects of food quantity and quality on population growth. The interplay between food quantity and biochemical food quality limitation seems to influence resource allocation patterns in order to optimise survival or reproduction, which may strongly affect population dynamics in variable environments. As opposed to exploring the function of a single nutrient via supplementation, using algae mixtures allowed us to assess food quality effects on consumer performance in a more natural context by taking potential interactive effects of multiple co‐limiting nutrients into account.